The Song of the Lark - Cather, Willa, 1873-1947 (Salt Lake City, UT : Project Gutenberg, 2008)
"The Song of the Lark" by Willa Cather is a novel written in 1915. It follows Thea Kronborg, a talented girl from a small Colorado town who dreams of becoming a musician. When a teacher discovers her remarkable singing voice, she leaves home to pursue vocal training in Chicago and beyond. The novel traces her artistic development and personal sacrifices as she climbs toward success, shedding relationships that no longer serve her ambition in the burgeoning American West. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Song_of_the_Lark_(novel)
Release date is 2008-06-27
Judith Boss, Marvin Peterson and David Widger
Keywords: Musical fiction; Young women -- Fiction; Bildungsromans; Chicago (Ill.) -- Fiction; Swedish Americans -- Fiction; Colorado -- Fiction; Opera -- Fiction; Children of clergy -- Fiction; Women singers -- Fiction